DESAIN INDUSTRI : STUDI MODEL PERLINDUNGAN HUKUM BERBASIS NILAI - Sukarmi Khudzaifah Dimyati M. Ali Mansyur (Masalah-Masalah Hukum, 2014)
Establishing model of protection of the law industral designs that meet the value of the social justice shlml be conducted, becoese industrial designs law are now transplantation Trip's Agreement and international conventions tempered capitalist uncongenial with result Indonesial nation. The impacted the registration of ime to time less deliver results satisfactory and heppened degradation creativity. District government not response and give such a plolicy of the granting of funds, stimulant registration with the “jemputbola”. Internalisation value of the Pancasila shlml be made as spirit and soul Indonesian nation to arrangements for the protection industrial designs vertion Indonesia as hyper development ceativity